PENGARUH DAYA TARIK DAN KEPUASAN NASABAH TERHADAP KUALITAS PELAYANAN KPR PADA BANK BTN KOTA BANDA ACEH - Muhammad Harris; Teuku Meldi Kesuma (Departemen Manajemen, 2019)
This research aims to knowing the influence of Attraction and Customer Satisfaction with KPR Service Quality at Bank BTN of Banda Aceh. In this research the data used are primary data and secondary data. While the population in this study is all customers who become KPR customers at Bank BTN of Banda Aceh. Where is the sampling in this research use method Non Probability Samplingwhich amounts to 100 customers. The analysis test used in this study isMultiple linear regressionwhere the results show thatAttractiveness has no effect and is not significant on Service Qualityand customer satisfaction has a significant effect on Service Quality